Pembelajaran Paduan Suara pada Lagu Wajib (Indonesia Raya) dalam Bentuk Unisono di Kegiatan Ektrakulikuler SMA Negeri 1 Koba - Juniar Ardiansyah; Deria Sepdwik; Rio Eka Putra (Departement of Mathematics Education, 2024)
The formulation of the problem in this study is How is the Learning of the Choir in the Indonesian Raya anthem in unison form in extracurricular activities at SMA Negeri 1 Koba? The purpose of this study was to find out how the choral learning of the Indonesia Raya obligatory anthem in the form of unison in extracurricular activities at SMA Negeri 1 Koba. The method used in this research is a qualitative approach. The data collection technique used is triangulation, namely observation, interviews, and documentation. Based on the results of the study it was found that this learning process occurs in stages consisting of planning, implementation and evaluation. The results of the planning have been described, namely the preparation of schedules, materials, methods and media. The results of the implementation have also been described, namely the application of the material, the application of the method. Followed by the overall result, namely evaluation.